Uji Aktivitas Antibakteri Ekstrak Daun Sirsak (Annona muricata L.) Terhadap Bakteri Staphylococcus aureus dan Salmonella typhi - Siahaan, Marshal Duva (Herbal Medicine Journal, 2023)
Soursop plants (Annona muricata L.) have been used for generations by some Indonesian people to treat diseases. Differences in environmental conditions where a plant grows can cause differences in the types and amounts of secondary metabolites contained in the plant. This study aims to determine the antibacterial activity of ethanol extract of soursop leaves against Staphylococcus aureus and Salmonella typhi and to determine the content of secondary metabolite compounds. The type of research is a laboratory experiment, extraction was carried out on soursop leaves using the maceration method using 70% ethanol solvent. The ethanol extract of soursop leaves was then screened for phytochemistry. Antibacterial activity tests were carried out using the disc paper diffusion method. This study used 5 concentrations, namely DMSO; Chloramphenicol; 10; 30; 50, 70%. The results of phytochemical screening of ethanol extract of soursop leaves contain secondary metabolite compounds in the form of saponins, terpenoids, steroids, flavonoids, tannins, alkaloids. Ethanol extract of soursop leaves can inhibit the growth of Staphylococcus aureus bacteria at a concentration of 30-70% while Salmonella typhi at a concentration of 70%.